Multi-Level and Multi-Dimensional Evaluation of Loss Reduction Effectiveness Based on Q-Order Orthogonal Fuzzy Group Decision-Making - Tang, Dongsheng; Xie, Yifeng; Wang, Zezhou; Jia, Dongli; Ren, Zhaoying (2025 2nd International Conference on Electrical Technology and Automation Engineering (ETAE), 2025)
With the increasing demand for new energy integration, in order to optimize the stable operation of the power grid and improve the absorption capacity of new energy power generation, a multi-level and multi-dimensional evaluation method of loss reduction effectiveness based on Q-order orthogonal fuzzy group decision-making is proposed in this paper. This method considers the economy, technology, environmental protection, and other aspects of different market subjects to establish a multi-level multi-objective model, and uses a Q-order orthogonal fuzzy multi-attribute decision-making analysis method for multi-attribute decision-making problems. It not only reflects the interest demands of different subjects, but also considers the impact of the collaborative operation of multiple subjects in the market on the loss reduction optimization of the distribution network.